Attenuation of Electromagnetic Waves Us- Ing Nanocomposites - Ali, Omar Mohammed; Mohammed, Omar Jassim; Zidan, Ibrahim Mohammed (Journal of Science in Medicine and Life, 2024)
Radar Absorbing Materials are composite materials that have the ability to absorb the energy of electromagnetic fields passing through them and thus reduce the waves reflected from the target. M) is one or more of the divalent ions such as (Ni, Mn, Cu, Cobalt, Co, Cd, Zn) [1]. This topic is considered one of the current im- portant topics in materials science due to the resulting common properties of insu- lation and conductivity and their entry into important technology applications [2]